PENGARUH AUDIT LAG, PROFITABILITAS, DAN KUALITAS AUDIT TERHADAP PEMBERIAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN WHOLESALE DAN RETAIL TRADE LISTING DI BEI PERIODE 2010-2012 - Al Azhar A; Hardi '; Ricky Rusydi Satriawan (PEKBIS, 2014)
The financial report users need valid information as based a primary decision.Auditor has responsibility to assess the ability of company to continue its businessactivity. Going Concern Audit Opinion is the opinion issued by auditor to evaluatewhether the company can maintain its ability in the future or not. This research isaimed to analyze Audit Lag impact, Profitbility, Quality Audit of audit to GoingConcern Audit Opinion. The sample is choose with sampling purpose technique.The population is all the wholesale and retail trade companies that are registered inIndonesian Stock Exchange since 2010-2012. Hypothesis testing use logisticregression. The result of testing, Quality Audit variable is significantly took effect toGoing Concern Audit Opinion acceptance. While Audit Lag and Profitability variablehave no significantly impact to going Concern Audit Opinion.Keywords: going concern audit opinion, audit lag, profitability, quality audit.